2017
DOI: 10.21873/cgp.20026
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-196b Accelerates Invasiveness of Cancer Cells in Recurrent Epithelial Ovarian Cancer Through Regulation of Homeobox A9

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…One study reported that overexpression of miR-196b may contribute to invasion activities of cancer cells in recurrent epithelial ovarian cancer by regulating the Homeobox A9 gene. 23 The methylation status of the miR-196b promoter region affects the level of miR-196b expression in tumors. In the study of gastric cancer, oral cancer, and melanoma, hypomethylation of the miR-196b promoter region increased the expression of miR-196b.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that overexpression of miR-196b may contribute to invasion activities of cancer cells in recurrent epithelial ovarian cancer by regulating the Homeobox A9 gene. 23 The methylation status of the miR-196b promoter region affects the level of miR-196b expression in tumors. In the study of gastric cancer, oral cancer, and melanoma, hypomethylation of the miR-196b promoter region increased the expression of miR-196b.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicate that hsa-mir196-b overexpression is bad for the cancer patient. For example, hsa-mir196-b overexpression is associated with poor prognosis in gastric cancer (Lim et al, 2013; Ge et al, 2014), and is also associated with accelerated invasiveness in epithelial ovarian cancer (Chong et al, 2017). Kanno et al, (2017) reported that hsa-mir-196b overexpression might be a prognostic biomarker for a bad outcome.…”
Section: Discussionmentioning
confidence: 99%
“…HOXA9 is a member of the HOX gene family reported to have crucial roles in regulating hematopoiesis ( 37 ). Previous studies have shown that HOXA9 was the target of miRNAs in acute myeloid leukemia ( 38 ), in cutaneous squamous cell carcinoma ( 39 ) and in ovarian cancer ( 40 ). Therefore, we investigated whether HOXA9 was a mediator of miR-429 tumor inhibition in OS cells.…”
Section: Discussionmentioning
confidence: 99%